The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.17221/462/2014-pse
|View full text |Cite
|
Sign up to set email alerts
|

The telemetric tracking of wild boar as a tool for field crops damage limitation

Abstract: The article presents the possibilities of visual and statistical outputs from the telemetric tracking of game: activity data, heat map, home regions, movement routes and the points of occurrence. Nowadays the methods of the telemetric tracking of game are also used for finding the best ways to eliminate damage caused by wild boar generally, and field crops damage specifically. From telemetrically gained data it is possible to study the local habits of wild boar and their preference of crops and cultivars in va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 12 publications
(11 reference statements)
0
6
0
Order By: Relevance
“…The statistical analyses did not consider fodder plants, as there were no precise data and the damage to these plants was estimated at only 0.1%. In turn, maize was distinguished, as this cereal is the most preferred food of wild boars (Amici et al 2012, Jarolímek et al 2014, Zeman et al 2018). The significance level was set at p ≤ 0.05.…”
Section: Discussionmentioning
confidence: 99%
“…The statistical analyses did not consider fodder plants, as there were no precise data and the damage to these plants was estimated at only 0.1%. In turn, maize was distinguished, as this cereal is the most preferred food of wild boars (Amici et al 2012, Jarolímek et al 2014, Zeman et al 2018). The significance level was set at p ≤ 0.05.…”
Section: Discussionmentioning
confidence: 99%
“…The collar was set to record GPS locations (~ 10 m accuracy) at 30 min intervals. The GPS locations were transmitted daily via the GSM module to a secure online database available at http://zver.agris.cz/en/, where the data were stored and backed up without the need of retrieving the collar (Jarolímek et al 2012;Jarolímek et al 2014). As a measure of the accuracy of each GPS location, the collar also recorded a dilution of precision (DOP) value, i.e.…”
Section: Data Collectionmentioning
confidence: 99%
“…Wild boar (Sus scrofa), a social mammal with a growing population throughout Europe (Massei et al, 2015;Keuling et al, 2016), is increasingly present in urban areas (Dinter, 1991;Cahill et al, 2003Cahill et al, , 2012Jansen et al, 2007;Podgorski et al, 2013). Wild boar frequently interfere with people, as they annoy garden owners (e.g., by rooting), can destroy agricultural crops (Amici et al, 2012;Ficetola et al, 2014;Jarolimek et al, 2014;Laznik and Trdan, 2014) and are potential transmitters of zoonotic diseases or diseases relevant to livestock (Fernández et al, 2006;Jansen et al, 2007;Chiari et al, 2015). Therefore, they are a useful model to study the ability of urban wildlife to perceive and respond to spatial variation in the landscape of fear.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, studying wild boar assists local authorities to develop appropriate management tools to minimize human-wildlife conflicts. Despite numerous studies on wild boar demonstrated substantial variation in home range size and kinetics of movements in natural and agricultural landscapes (Dardaillon and Beugnon, 1987;Cousse et al, 1992;Janeau et al, 1995;Thurfjell et al, 2013;Jarolimek et al, 2014;Morelle et al, 2014Morelle et al, , 2015, studies of urban wild boar are rare (Cahill et al, 2003(Cahill et al, , 2012Podgorski et al, 2013;Stillfried et al, 2017a,b).…”
Section: Introductionmentioning
confidence: 99%